The Legal Conflict on Registration of Inter-Religious Marriages Before & After SEMA No. 2 of 2023 - Jasmine, Adira Mutiara; Ramadhani, Dwi Aryanti (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2024)
Registration of interfaith marriages in Indonesia has become an interesting legal issue to study, especially after the publication of Supreme Court Circular Letter (SEMA) No. 2 of 2023. This SEMA provides confirmation that unregistered interfaith marriages will not be recognized by the state, causing the emergence of legal conflicts related to the legal status of previously executed marriages. This research aims to analyze the differences in the perception of marriage before and after SEM|A No . 2 YEAR 2023, as well as legal impacts arising from SEM provisions A. The research method used is a normative research method with a short form of quantitative action, a short form of legislation draft by analyzing various regulations related to research issues. The research results reveal that although SEMA No. 2 of 2023 does not apply retroactively, couples who were married before the issuance of SEMA will still have their marriage recognized as valid by the state. However, couples who marry after the SEMA has been issued and cannot register their marriage face legal uncertainty, which impacts inheritance rights, the legal status of the marriage, and the protection of children born from the marriage.